Periodontal Treatment for Chronic Periodontitis With Rheumatoid Arthritis - Sivasankari Thilagar; Ramakrishnan Theyagarajan; Maryam H. Mugri; Hammam Ahmed Bahammam; Sarah Ahmed Bahammam; Maha A. Bahammam; Pradeep Kumar Yadalam; A. Thirumal Raj; Shilpa Bhandi; Shankargouda Patil (Elsevier, 2022)
Background: History of rheumatoid arthritis (RA) increases risk of periodontal diseases. A pro-inflammatory condition noted in periodontitis is considered a trigger for RA. Thus, periodontal treatment aimed at attenuating the pro-inflammatory state could aid in potentially reducing the risk of RA. Aims: The objective of this research was to assess the effect of periodontal therapy on rheumatoid factor, Disease Activity Score-28, anti-citrullinated protein antibody, and C-reactive protein levels in patients with chronic periodontitis (CP) and RA. Materials and methods: The sample consisted of 28 patients with CP and RA. The study was designed to be a double-blind, randomised controlled clinical study. The samples were randomly categorised to either the treatment group (n = 13) or the control group (n = 15). CP status (plaque index, bleeding on probing, probing pocket depth, clinical attachment loss), clinical rheumatologic status (Disease Activity Score), and biochemical status (C-reactive protein, anti-citrullinated protein antibody, and rheumatoid factor) were assessed at baseline and at follow-up at 8 to 12 weeks. Results: The treatment group showed a highly statistically significant reduction in bleeding on probing (P < .005), probing pocket depth (P < .001), plaque index (P < .001), and C-reactive protein (P < .001); a gain in the clinical attachment loss (P < .001) and an improvement in Disease Activity Score-28 (P = .001) were observed at reassessment following nonsurgical periodontal treatment as compared to the control group. However, blood serum anti-citrullinated protein antibody (P = .002) and rheumatoid factor levels (P = .351) were found to increase from baseline to 8 to 12 weeks following subgingival scaling and root planing. Conclusions: Reduction of inflammation in the periodontium by nonsurgical periodontal therapy did not reduce anti-citrullinated protein antibody and rheumatoid factor levels. However, it has shown improvement in periodontal conditions, and remarkable changes were observed in the clinical Disease Activity Score and C-reactive protein levels of individuals with RA.